2019
DOI: 10.1038/s41598-019-52551-5
|View full text |Cite
|
Sign up to set email alerts
|

Fengycin induces ion channels in lipid bilayers mimicking target fungal cell membranes

Abstract: The one-sided addition of fengycin (FE) to planar lipid bilayers mimicking target fungal cell membranes up to 0.1 to 0.5 μM in the membrane bathing solution leads to the formation of well-defined and well-reproducible single-ion channels of various conductances in the picosiemens range. FE channels were characterized by asymmetric conductance-voltage characteristic. Membranes treated with FE showed nonideal cationic selectivity in potassium chloride bathing solutions. The membrane conductance induced by FE inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…It is known that the antifungal cyclic lipopeptide produced by Bacillus subtilis , Fen, acts by making the plasma membrane of the target cell more permeable ( Vanittanakom et al, 1986 ; Patel et al, 2011 ). The Fen-induced increase in membrane permeability is related to the formation of ion channels of various conductances and non-ideal cationic selectivity ( Zakharova et al, 2019 ). It was also shown that the alteration in membrane dipole potential does not affect the pore-forming ability of this lipopeptide while the membrane adsorption of small molecules that decreased the lipid packing density enhances the steady-state Fen-induced transmembrane current ( Zakharova et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known that the antifungal cyclic lipopeptide produced by Bacillus subtilis , Fen, acts by making the plasma membrane of the target cell more permeable ( Vanittanakom et al, 1986 ; Patel et al, 2011 ). The Fen-induced increase in membrane permeability is related to the formation of ion channels of various conductances and non-ideal cationic selectivity ( Zakharova et al, 2019 ). It was also shown that the alteration in membrane dipole potential does not affect the pore-forming ability of this lipopeptide while the membrane adsorption of small molecules that decreased the lipid packing density enhances the steady-state Fen-induced transmembrane current ( Zakharova et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Fen-induced increase in membrane permeability is related to the formation of ion channels of various conductances and non-ideal cationic selectivity ( Zakharova et al, 2019 ). It was also shown that the alteration in membrane dipole potential does not affect the pore-forming ability of this lipopeptide while the membrane adsorption of small molecules that decreased the lipid packing density enhances the steady-state Fen-induced transmembrane current ( Zakharova et al, 2019 ). Thus, the significant effects of C3, C6, and C8 on lipid packing ( Figure 3 and Table 4 ) indicate their potential applications for up-regulating the pore-forming ability of Fen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mode of action of many Bacillus spp. NRPS-and PKS-derived anitmicrobials is through membrane perturbation or depolarization (15), e.g., fengycin (41) and iturin A (42), blockage of peptidoglycan biosynthesis, e.g., bacilysin (34), or selective inhibition of protein synthesis, e.g., difficidin (34). Regardless of mechanism, both co-culture and cell-free supernatant experiments demonstrated that D4 was capable of overcoming the T1 NRPS-PKS inhibitory activity, with growth levels reaching those obtained for untreated cultures.…”
Section: Synthesis and Secretion Of Antimicrobial Compounds By Membermentioning
confidence: 99%